Strategic Health Diplomacy: An Indonesia’s Approach in Securing COVID-19 Booster Vaccine Supplies - Sari, Deasy Silvya; Halimah, Mas; Akim, Akim; Maximillian, Renata; Muawal, Fakhri Sabiq; Lie, Nathanael Jusac (Jurnal Hubungan Internasional, 2024)
The COVID-19 pandemic has necessitated a rapid and coordinated international response, particularly in the procurement of life-saving vaccines. As nations endeavor to protect their populations, health diplomacy emerges as a pivotal strategy. This study provides an in-depth analysis of Indonesia’s health diplomacy strategy in securing booster vaccines for COVID-19, a critical component in mitigating the impact of the pandemic. Employing a qualitative research method, this investigation synthesized data from comprehensive literature reviews and focus group discussions (FGDs) to construct a nuanced understanding of Indonesia’s approach. The findings illuminated the multifaceted nature of Indonesia’s health diplomacy, operating on bilateral, regional, and global stages. A notable outcome of these diplomatic efforts was the acquisition of 510,000,000 doses of the booster vaccines scheduled for distribution by the end of 2022. The research identified a supportive diplomatic ecosystem underpinned by the universal necessity for vaccine access, transcending national borders. This environment was characterized by a coalition of researchers advancing vaccine knowledge, complexities surrounding vaccine procurement, and the operationalization of international initiatives such as the COVAX Facility and the ASEAN COVID-19 Response Fund. The intricacies of Indonesia’s diplomatic engagements revealed the importance of collaborative frameworks in addressing global health crises. The study contributes to the discourse on health diplomacy by highlighting the mechanisms and outcomes of Indonesia’s vaccine procurement strategy, offering insights into the role of diplomacy in pandemic preparedness and response.